Efektivitas Program Kelas Merajut dalam Pengembangan Perpustakaan Berbasis Inklusi Sosial untuk Pembangunan Sosial-Ekonomi Masyarakat di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Aldi, Fauzi; Erlianti, Gustina (Lembaga Yasin AlSys, 2025)
In the midst of globalization and technological advances, libraries are required to transform into centers of social inclusion that are able to encourage socio-economic development. This study aims to describe the effectiveness of the knitting class program in developing a social inclusion-based library implemented by the West Sumatra Provincial Archives and Libraries Office. The research method used is a quantitative approach with a descriptive survey design. The research sample was 30 program participants who were determined using the saturated sample technique. Data were collected through observation, interviews, and the distribution of Likert-scale questionnaires that had been tested for validity and reliability. Data analysis techniques used descriptive statistics, including editing, tabulation, frequency distribution, and percentages. To maintain data validity, triangulation techniques and discussions with peers were applied. The results showed that the knitting class program was rated effective based on five key indicators: program understanding, targeting accuracy, timeliness, goal achievement, and tangible changes. Participants demonstrated a high understanding of the empowerment goals, as well as experiencing increased skills and tangible economic benefits from the program. In addition, the program implementation ran on time and was able to form a new social network through the knitting community. In conclusion, the knitting class program contributed positively to the development of a social inclusion-based library and became a good practice in supporting the socio-economic development of the community in a sustainable manner.